Increased Oxidative Stress Is Responsible for Severer Cerebral Infarction in Stroke‐Prone Spontaneously Hypertensive Rats - Zhang, Xiu‐Hua (CNS Neurosci Ther, 2011)
Aims: To examine the role of increased oxidative stress in the pathogenesis of cerebral infarction in stroke in stroke‐prone spontaneously hypertensive rats (SHR‐SP). Methods: The differentially expressed brain protein profile was examined in spontaneously hypertensive rats (SHR) (control group) and SHR‐SP using two‐dimensional fluorescent difference gel electrophoresis (2D‐DIGE). In addition, oxidative stress indicators including total antioxidation capacity (TAC), glutathione peroxidase (GPx) activity, and maleic dialdehyde (MDA) were also measured. Lastly, SHR‐SP were randomly divided into untreated and treated (vitamins C (200 mg/kg/day) and E (100 mg/kg/day)) groups. After treatment for 4 weeks, half of the animals were sacrificed for detection of TAC, GPx, and MDA. The remaining rats underwent middle cerebral artery occlusion (MCAO) and the infarct areas were measured. Results: Compared with SHR, the infarct area of SHR‐SP was larger (P < 0.01), and the antioxidative proteins including glutathione S‐transferase (GST) Pi2 and GST A5 were lower; TAC and GPx activities were decreased and MDA levels. Treatment with vitamins C and E decreased MDA, and increased TAC and GPx activity significantly in SHR‐SP, while also decreasing the infarct area (P < 0.01). Conclusions: Our findings indicate that oxidative stress plays an important role in the pathogenesis of cerebral ischemia.